Sexual function after radical cystectomy in males with bladder carcinoma: a six-year longitudinal single-centre study - Pronk, Claudia E.; Albers, Leonore F.; Kuijper, Lothar D. J.; Hendricksen, Kees; Nicolai, Melianthe P. J. (Frontiers in Urology, 2023)
Introduction Little is known about the long-term effects on sexual function (SF) after radical cystectomy (RC) in bladder carcinoma (BC) patients. Aim To assess the course of SF in BC patients who underwent RC, and individual characteristics that influence the sexual outcome during a six-year follow-up. Methods In this longitudinal study, 62 BC patients treated with RC were included between 2008 and 2022. Patients filled out validated questionnaires as part of the regular care at baseline, three months, six months, 12 months and thereafter yearly post RC. Outcome measures To determine the sexual function, the International Index of Erectile Function questionnaire was filled in and a linear mixed model for repeated measures was conducted. The analysed clinical variables included sexual preserving cystectomy (SPC), age, type of diversion, treatment, comorbidities, tumour status, smoking habits, patient status and open- or robot-assisted RC. A Generalised Linear Mixed Model was used to evaluate the impact on Quality of Life with the QLQ-C30 questionnaire. Results After an initial decrease of sexual function post-RC, no change in SF was seen during the six years of follow-up. A statistically significant difference in sexual health was found between SPC and standard RC (p=0.015), which was time-dependent. Patients with an orthotopic ileal neobladder experienced a significantly better SF than those with a Bricker’s ileal conduit (p=<0.001). A younger age also seemed to yield beneficial outcomes regarding SF (p=0.004). Other analysed clinical variables did not influence the course of SF. A statistically significant positive correlation was found between Quality of Life- and SF scores (p=0.004). Robot-assisted RC resulted in higher Global Health scores than open RC (p=0.001). Conclusions RC has a severe impact on sexual function. Although SPC, collinear with the use of an orthotopic ileal neobladder and younger patient age show better outcomes in SF, erectile dysfunction post-RC is moderate to severe in the vast majority of patients.